“My Vision Isn’t The Only One” - Riley Drake; Renae Mayes; Abby Smith; Ingrid Lyberg (Journal for Social Action in Counseling and Psychology)
School counseling is built on the American School Counselor Association National Model (2019, 2025), which includes heavy emphasis on individualist-focused student standards and isolationist practice (Drake et al., 2024b). While the field has undergone some revision, we continue to lack methods for visioning and visions for abolition in our praxis. Without liberatory visions for abolition, our traditional approaches and models of school counseling will only prefigure more racial capitalism, more white supremacy, and more state violence in schools. As part of a larger, year-long Critical Participatory Action Research project, this article focuses on the abolitionist visioning generated by a community of practice, including school counselors, community organizers, and a school counselor educator, using arts-based exploration. Our findings center the collective analysis and meaning-making of our community of practice, elevating the visions of on-the-ground school counselors and organizers and honoring local wisdom to guide practice rather than relying on Westernized, meritocratic school counseling models.